THE EFFECT OF BANK SERVICE QUALITY AND PRICE ON CUSTOMER DECISIONS AT PT BANK BNI WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Tasyah Maulida Sari Tampubolon; Fadli Fadli; Erman Munir (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the effect of bank service quality and price on customer decisions at PT Bank BNI, with brand image as an intervening variable. As one of the major banks in Indonesia, Bank BNI faces challenges in maintaining the appeal of its banking products amidst the increasing competition, especially with the rise of fintech-based financial services offering convenience and speed in transactions. The quality of service provided by the bank and its competitive pricing structure are crucial factors influencing customers' decisions to choose and continue using banking products. However, a strong brand image is believed to strengthen the relationship between service quality and price on customer decisions. Therefore, this study adopts a quantitative approach using path analysis to examine the relationships among these variables. Data were collected through surveys involving Bank BNI customers who use various banking services. The results of this study are expected to provide deeper insights into the role of service quality, price, and brand image in shaping customer decisions, and offer recommendations for the bank to enhance its competitiveness in an increasingly digital market.